Increased expression of REV7 in small cell lung carcinomas and its association with tumor cell survival and proliferation. Issue 1 (28th October 2020) - Sanoyama, Itaru; Sakurai, Yasutaka; Ichinoe, Masaaki; Hoshino, Akiyoshi; Kesen, Yurika; Kato, Takuya; Numata, Yoshiko; Umezawa, Atsuko; Jiang, Shi‐Xu; Murakumo, Yoshiki
Abstract : REV7 is involved in multiple biological processes including DNA damage tolerance, cell cycle regulation and gene expression, and is an accessory subunit of the mutation‐prone DNA polymerase ζ. It has been reported that REV7 expression is associated with poor prognosis in several human cancers. The aim of this study is to investigate the significance of REV7 in lung carcinogenesis. Immunohistochemical analyses of surgically resected lung cancer specimens revealed that REV7 shows an increased expression in small cell lung carcinomas (SCLCs) when compared with other histological types of lung carcinoma. Association between REV7 expression levels and clinicopathological factors was investigated using SCLC cases with or without surgical resection. Our analyses revealed that high REV7 expression significantly correlated with tumor cell proliferation, assessed by Ki‐67 labeling indices, and was negatively associated with distant metastasis and extensive‐stage disease. No significant association was detected between REV7 expression and other factors, including prognosis or response to chemoradiotherapy in SCLC. Increase in REV7 expression in SCLC was confirmed using SCLC cell lines. In addition, siRNA‐mediated depletion of REV7 activated the apoptotic pathway and suppressed cell growth in SCLC cells. These results suggest that REV7 plays an important role in tumor cell survival and proliferation in SCLC.